Influence of storage temperature and time in storage on pigment content of potato (Solanum tuberosum L.) - Alenazi, Mekhled M., author; Hughes, Harrison G., advisor; Holm, David G., advisor (Colorado State University. Libraries, 2005)
Anthocyanins are responsible for different colors in many plant species including potato tubers. They are also one of the important components in human health as antioxidants. Important factors that can affect anthocyanin concentration in potato tubers are storage temperature and the length of storage. The influence of storage temperature and time in storage on tuber anthocyanin concentration was investigated in seven potato genotypes. These genotypes were cultivars All Blue and Yukon Gold as well as VC0967-SR/Y, Purple Majesty (CO9I6S-3P/P), Mountain Rose (CO94183-1R/R), VC1002-3W/Y and CO97232-2R/Y. Tubers of the seven genotypes were stored at 4°C and 10°C for 0, 4, 6, 8, 10, 12, 16, 20 and 24 weeks . Both fresh and freeze-dried samples of the tubers were evaluated for each of the temperature and time treatment combinations. Extractable anthocyanins were obtained in only three genotypes, CO94183-1R/R, CO94165-3P/P and "All Blue", as determined by the UV/Vis Molecular Device Spectra Max Plus 384 spectrophotometer. There was an increase in anthocyanin concentration with increased time in storage for both fresh and freeze-dried samples (P<0.0001). However, tubers stored in the cooler at (4°C) had much higher levels of anthocyanin than those tubers stored at 10°C. Increased levels of anthocyanins in cold-stored tubers are likely associated with the conversion of starch to sugar (so called "cold sweetening") and subsequent conversion to anthocyanins. More anthocyanins were extracted from freeze-dried tuber samples than fresh samples. Both techniques exhibited a similar trend in that an increase in length of time in storage had a similar level of increase in anthocyanin concentration. Extraction of anthocyanins from freeze-dried tissue is more efficient and effective than using fresh tissue for evaluation of anthocyanin concentration in potato tubers.
Covers not scanned.
Keywords: Potatoes -- Storage